A NEED OF ENGLISH TEACHER PROFESSIONAL COMPETENCE IN 21ST CENTURY - Nurhalimah Nurhalimah; Hendi Hidayat; Ahmad Rifai (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Professional competence of an English teacher in this century has many problems, such as lack of English teacher development program and the English teacher problems in using technology. In literature, professional competence indicators review is very lack and research reported about a need analysis of teacher professional competence was not found. Moreover, it does not related to notion of 21st century. So, the objective of the research is to find out the need analysis of professional competence of English teachers in the 21st century. The method of the research is qualitative research. The interview was conducted to English teachers at a Vocational High School was collected to get the data. The interview data will be analyzed by three steps: reduction, display and conclusion. The need of English teacher in professional competence are (1) Being up to date towards English subject; (2) Empowering things related to develop curriculum; (3) Developing materials based on the students and school condition and situation; (4) Conducting a research; (5) Promoting ICT skills; and (6) Learning and implementing the educational foundation. Those need analysis can be useful to improve the quality of English teacher in the 21st century education in Indonesia.